Does Business Sustainability Mediate the Effect of Women’s Micro Entrepreneurship on Family Welfare? - Aas Nurasyiah; Hilda Monoarfa; Ripan Hermawan; Firmansyah Firmansyah; Rahmayati; Shafinar Ismail (Journal of Islamic Economics and Business, 2026)
This study aims to develop a holistic model of family welfare among women micro-entrepreneurs by examining the effects of Islamic microfinance, women’s empowerment, spiritual motivation, and digital technology adoption, with business sustainability serving as a mediating variable. Unlike previous studies that predominantly examine the direct effects of financial and non-financial resources on business performance or welfare, this study integrates financial, technological, empowerment, and spiritual dimensions into a single model and investigates business sustainability as the mechanism linking these factors to family welfare. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through purposive sampling from 200 women micro-entrepreneurs in West Java, Indonesia. The results demonstrate that digital technology adoption and spiritual motivation have positive and significant effects on business sustainability, whereas women’s empowerment has a significant negative effect. Islamic microfinance does not significantly affect business sustainability. Digital technology adoption, spiritual motivation, and business sustainability have positive and significant effects on family welfare, while Islamic microfinance and women’s empowerment have no significant direct effects. The mediation analysis reveals that business sustainability significantly mediates only the relationship between digital technology adoption and family welfare. However, it does not mediate the effects of Islamic microfinance, women’s empowerment, or spiritual motivation on family welfare. These findings highlight digital technology adoption as a critical pathway through which sustainable micro-enterprises can improve the welfare of women entrepreneurs’ families.